The improvement of morphological parameters by the introduction of martial arts techniques in physical education and sports lessons - Andreea - Gabriela Lazăr (Editura Univeristatii "Stefan cel Mare" din Suceava, 2020)
Tae Bo is one of the most impressive and demanding training methods, which is also based on the principles promoted by the martial arts. From the point of view of the mental and physical demands required by this method of preparation, Tae Bo lessons are a real challenge for the students and it bring many beneficial effects in their development plan. In the present research, we started from the hypothesis that teaching martial arts techniques and combining them with other motor structures, in an aerobic program performed on music, will lead to the improvement of the morphological indices of the students from the experimental group. The experiment and control group were made up of 24 students from the Accounting and Management Informatics specialization. The research was carried out during a university semester, and at the end it was shown that the kicks and the punches performed on all trajectories, have had beneficial effects on the cardiovascular and respiratory systems, but at the same time they have contributed to the harmonious development of the body resulting in better values of the measured morphological indices.